Edukasi Peraturan Lalu Lintas, Rambu dan Pelanggaran Lalu Lintas SMK Negeri 12 Samarinda - Samuel Marbun; Mhd Rayhan Sakban (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The high rate of traffic violations committed by the public, particularly students and young drivers, highlights the need for improved education on road safety. A lack of understanding of traffic signs, road markings, and the legal consequences of traffic violations is one of the main causes of road accidents. This community service activity aims to improve public knowledge and awareness regarding traffic regulations, types of traffic signs, and the impact of traffic violations on driving safety. The methods used include educational sessions, interactive discussions, traffic sign recognition simulations, and evaluation through pre-tests and post-tests. The activity had 45 participants, all of whom were students. The results of the activity showed an average increase in participants’ scores from 61.33 on the pre-test to 84.89 on the post-test. Additionally, participants demonstr ated improved understanding of the functions of traffic signs, types of violations, and the importance of a culture of traffic discipline. This educational program is effective in raising awareness of driving safety & can serve as model for sustainable community development